High Prevalence of Self-Reported Dentin Hypersensitivity and its Associated Factors in Peruvian University Students - Corrales-Mattos-Simão , Carolina (2026)
This study aimed to determine the prevalence of self-reported dentin hypersensitivity and its association with sociodemographic, clinical, dental, dietary, and lifestyle factors among Peruvian university students. An observational, cross-sectional, and analytical design was applied to a sample of 600 students who completed a validated, self-administered digital questionnaire with 37 items distributed across five dimensions, plus a section on dentin hypersensitivity. The outcome variable was self-reported tooth sensitivity, defined as pain in response to thermal, mechanical, or chemical stimuli, acknowledging the inherent limitations of self-reported data. The overall prevalence was 68.5%, and 39.4% of participants reported sensitivity to two or more stimuli. In bivariate analyses, hypersensitivity was significantly associated with gastric acidity, dry mouth, and frequent consumption of acidic foods, whereas snoring and orthodontic treatment showed marginal trends. In multivariable logistic regression, gastric acidity (OR = 1.86; 95% CI: 1.26-2.73), dry mouth (OR=2.16; 95% CI: 1.37-3.42), and snoring (OR=1.65; 95% CI: 1.02-2.68) remained independent associated factors. The final model exhibited good overall fit and high sensitivity, though low specificity, with a moderate discriminative capacity (AUC=0.668). In conclusion, self-reported dentin hypersensitivity among university students showed a high prevalence, mainly associated with gastric acidity, dry mouth, and snoring, with additional trends related to orthodontic treatment and frequent intake of acidic foods, and the findings should be interpreted considering the limitations of self-reported measurements.